Anni Albers, Ann Coxon, Briony Fer and Maria Müller-Schareck (eds) (2018). Issue 3 (1st December 2020) - Bothe, Lauren
Review of: Anni Albers, Ann Coxon, Briony Fer and Maria Müller-Schareck (eds) (2018)London: Yale University Press in association with Tate Publishing, 192 pp., 190 colour illus., ISBN 978-0-30023-725-2, h/bk, £38.27/50.00